(untitled) (Journal of Universal Science Research, 2025)
Clinical grading systems that use clinical characteristics, as well as nomograms, do not have the accuracy to guide treatment decisions for prostate cancer (prostate cancer). There is a critical need to identify biomarkers that can more accurately stratify men with primary prostate cancer